1987
DOI: 10.1515/cclm.1987.25.11.779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Lipotropin, β-Endorphin, γ2-Melanotropin and Corticotropin on Steroid Production by Isolated Human Adrenocortical Cells

Abstract: Summary:Normal human adrenocortical cells (from multi-organ donors) were incubated with corticotropin (tetracosactide), highly purified human ß-lipotropin, synthetic human ß-lipotropin, y 2 -melanocyte stimulating hormone and ß-endorphin. Corticotropin stimulated cortisol, aldosterone and 18-hydroxycorticosterone production starting at " 12 -10" 11 mol/1 in normal adrenocortical cells. Purified human ß-lipotropin also stimulated steroidogenesis but 100 -lOOOfold higher concentrations of the peptide were needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…We speculate so because Lam berts et al [6] reported a higher adrenocortical respon siveness to ACTH in vitro in patients with Cushing's disease having macronodular adrenocortical hyperplasia than in those with diffuse hyperplasia. Second, it is also possible that in the present case various POMC-derived peptides implicated in the regulation of adrenocortical function [7][8][9][10][11] may have significantly affected cortisol secretion independently of or in concert with ACTH.…”
Section: Discussionmentioning
confidence: 88%
“…We speculate so because Lam berts et al [6] reported a higher adrenocortical respon siveness to ACTH in vitro in patients with Cushing's disease having macronodular adrenocortical hyperplasia than in those with diffuse hyperplasia. Second, it is also possible that in the present case various POMC-derived peptides implicated in the regulation of adrenocortical function [7][8][9][10][11] may have significantly affected cortisol secretion independently of or in concert with ACTH.…”
Section: Discussionmentioning
confidence: 88%